A modified physical model of high-strength water hydraulic artificial muscles considering the effects of geometry and material properties. (January 2022) - Zhang, Zengmeng; Che, Jinkai; Liu, Peipei; Jia, Yunrui; Gong, Yongjun
Compared with pneumatic artificial muscles (PAMs), water hydraulic artificial muscles (WHAMs) have the advantages of high force/weight ratio, high stiffness, rapid response speed, large operating pressure range, low working noise, etc. Although the physical models of PAMs have been widely studied, the model of WHAMs still need to be researched for the different structure parameters and work conditions between PAMs and WHAMs. Therefore, the geometry and the material properties need to be considered in models, including the wall thickness of rubber tube, the geometry of ends, the elastic force of rubber tube, the elongation of fibers, and the friction among fiber strands. WHAMs with different wall thickness and fiber materials were manufactured, and static characteristic experiments were performed when the actuator is static and fixed on both ends, which reflects the relationship between contraction force and pressure under the different contraction ratio. The deviations between theoretical values and experimental results were analyzed to investigate the effect of each physical factor on the modified physical model accuracy at different operating pressures. The results show the relative error of the modified physical model was 7.1% and the relative error of the ideal model was 17.4%. When contraction ratio is below 10% and operating pressure is 4 MPa, the wall thickness of rubber tube was the strongest factor on the accuracy of modified model. When the WHAM contraction ratio from 3% to 20%, the relative error between the modified physical model and the experimental data was within ±10%. Considering the various physical factors, the accuracy of the modified physical model of WHAM is improved, which lays a foundation of non-linear control of the high-strength, tightly fiber-braided and thick-walled WHAMs.